Implementation of Risk Management: A Qualitative Study on Bank Syariah Indonesia - Aisyah Sayidul Lintang; Faujiah, Ani (ICO EDUSHA, 2024)
This study aims to explore the implementation of risk management at Bank Syariah Indonesia (BSI) using a qualitative literature review approach. The research addresses the core issue of managing complex risks in Islamic banking, focusing on six key risks: credit, liquidity, market, operational, reputational, and Sharia compliance risks. The study was motivated by the urgent need to understand Sharia-based risk management strategies amidst the dynamics of the modern financial industry. The findings reveal that BSI has integrated Sharia principles with conventional risk management frameworks. However, challenges such as low Islamic financial literacy, technological adaptation, and consistency in Sharia compliance remain significant barriers. This study provides conceptual insights and recommendations to enhance risk management through technological innovation, public education, and the development of more comprehensive regulations.